1994
DOI: 10.1017/s002211209400203x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of vortical structures in a homogeneous shear flow

Abstract: The mechanism of generation, development and interaction of vortical structures, extracted as concentrated-vorticity regions, in homogeneous shear turbulence is investigated by the use of the results of a direct numerical simulation of the Navier-Stokes equation with 1283 grid points. Among others, a few of typical vortical structures are identified as important dynamical elements, namely longitudinal and lateral vortex tubes and vortex layers. They interact strongly with each other. Longitudinal vortex tubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 11 publications
8
66
0
Order By: Relevance
“…The regeneration cycle just analyzed here for the statistical steady state phase is very similar to that described by Kida & Tanaka [10] for the early stages of evolution of the flow from isotropic initial conditions, suggesting that the operating mechanisms are substantially identical.…”
Section: Regeneration Cycle Of Vortical Structuressupporting
confidence: 74%
See 2 more Smart Citations
“…The regeneration cycle just analyzed here for the statistical steady state phase is very similar to that described by Kida & Tanaka [10] for the early stages of evolution of the flow from isotropic initial conditions, suggesting that the operating mechanisms are substantially identical.…”
Section: Regeneration Cycle Of Vortical Structuressupporting
confidence: 74%
“…[9] discussed streamwise vortices and high and low speed streaks commenting on the similarities with the buffer region of wall bounded flows. In a more recent work Kida & Tanaka [10] proposed a regeneration mechanism for the streamwise vortices and pointed out the role of vortex sheet instability in the formation of new vortices. The present analysis deals with the same issues, but it is focused on the statistical steady state regime of the flow.…”
Section: Regeneration Cycle Of Vortical Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest shear flow is unbounded homogeneous shear turbulence (HST), which, unfortunately, does not have an asymptotic statistically stationary state. Ideal HST in unbounded domains grows indefinitely, both in intensity and in length scale (Champagne, Harris & Corrsin 1970;Harris, Graham & Corrsin 1977;Lee et al 1990;Kida & Tanaka 1994), and simulations are typically discontinued as the growing length scale approaches the size of the computational box (Rogers & Moin 1987). However, Pumir (1996) extended the simulation to longer times and reached a statistically stationary state (SSHST) in which the largest-scale motion is constrained by the computational box and undergoes a succession of growth and decay phases of the kinetic energy and the enstrophy, reminiscent of the bursts in wall-bounded flows.…”
mentioning
confidence: 99%
“…For example, Rogers & Moin (1987) showed typical 'hairpin' structures under shear rates comparable to those in the logarithmic layer of wall-bounded flows, and Lee et al (1990) found that higher shear rates, comparable to those in the buffer layer, result in structures similar to near-wall velocity streaks (Jimenez, 2013b). Those structures are known to play crucial roles in transition and in maintaining shear-induced turbulence (Jiménez & Moin, 1991;Jiménez, 1994;Hamilton et al, 1995;Waleffe, 1997), and Kida & Tanaka (1994a) proposed a generation mechanism for the streamwise vortices in transient HST that recalls those believed to be active in wall turbulence.…”
Section: Numericsmentioning
confidence: 99%